MEASURING LEGAL PROTECTION FOR VICTIMS OF DISCRIMINATION AGAINST PERSONS WITH DISABILITIES - Rahmadhani, Chalista Nadine; Nabila, Avrilia; Aldiyanti, Ira; Mayasari, Dinda; Aditriani, Iffani Fatma; Prehantoro, Puthut (Realism: Law Review, 2025)
Persons with disabilities in Indonesia still face discrimination in various aspects of life despite the existence of regulations aimed at protecting their rights. Law No. 8/2016 on Persons with Disabilities is present as a legal instrument that specifically regulates the protection of this vulnerable group, but in practice it often overlaps with the provisions in the Criminal Code (KUHP) which are general in nature. The fundamental differences in approaches, definitions of criminal offenses, and legal sanctions between the two regulations lead to norm conflicts that have an impact on legal uncertainty and ineffectiveness of protection for persons with disabilities. This research uses a normative method with a regulatory and conceptual approach to analyze the conflict between Law No. 8/2016 and the Criminal Code in the context of legal protection for victims of discrimination against persons with disabilities. The results show that law enforcement officials more often use the Criminal Code in handling discrimination cases, so that the provisions in Law No. 8 of 2016 are not optimally applied. Therefore, legal harmonization is needed by applying the principle of lex specialis derogat legi generali so that Law No. 8 of 2016 can be the main reference in the protection of persons with disabilities. In addition, increasing the understanding of law enforcement officials and socialization to the community are also important steps to ensure more effective legal protection.